Investigation of language use in academic writing of grade 10 learners in English First Additional Language (EFAL) classroom - Petja, Phomolo Matsobane (My University, 2023)
This study investigated the challenges experienced by Grade 10 learners in the usage of English as the first additional language in classroom academic writing. Qualitative methodology was used to conduct this study where responses from a sample of 10 learners and 2 EFAL teachers were obtained. The participants were purposefully sampled from a secondary school in Tweefontein. The researcher collected data using the semi-structured interviews and document analysis. Selected teachers were interviewed and learners were given an essay writing task. The data was analysed using the inductive thematic data analysis method. The study‟s findings point to social media as the major factor that contributes to the learners‟ usage of social language in academic essay writing. Contraction was found to be the most common language issue in the learners‟ academic writing. The study recommends that stakeholders such as the Department of Education, teachers, parents and learners should work together in order to improve the learners‟ usage of language in academic writing.
Thesis (M. A. (Language Education)) -- University of Limpopo, 2023
Keywords: Language usage; Academic writing; Social language/non-academic writing; English First Additional Language; Learners; English language -- Usage; Academic writing -- Ability and testing